2020
DOI: 10.3233/jad-200514
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Dispersion Is Not Associated with Cerebrospinal Fluid Biomarkers of Alzheimer’s Disease: Results from the European Prevention of Alzheimer’s Dementia (EPAD) v500.0 Cohort

Abstract: Background: Cognitive dispersion, variation in performance across cognitive domains, is posited as a non-invasive and cost-effective marker of early neurodegeneration. Little work has explored associations between cognitive dispersion and Alzheimer’s disease (AD) biomarkers in healthy older adults. Even less is known about the influence or interaction of biomarkers reflecting brain pathophysiology or other risk factors on cognitive dispersion scores. Objective: The main aim of this study was to examine whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 42 publications
0
12
1
Order By: Relevance
“…Results from the few existing studies that have examined associations of IIV and AD biomarkers or neuropathology have been mixed. An autopsy study showed that higher IIV was significantly associated with more severe neurofibrillary tangle pathology and trended toward an association with more severe neuritic plaques ( Malek-Ahmadi et al, 2017 ) whereas another study found that IIV was not associated with in vivo CSF-based markers of AD pathology cross-sectionally ( Watermeyer et al, 2020 ). A unique aspect of the current study is the integration of longitudinal data, CSF AD biomarkers, and CBF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from the few existing studies that have examined associations of IIV and AD biomarkers or neuropathology have been mixed. An autopsy study showed that higher IIV was significantly associated with more severe neurofibrillary tangle pathology and trended toward an association with more severe neuritic plaques ( Malek-Ahmadi et al, 2017 ) whereas another study found that IIV was not associated with in vivo CSF-based markers of AD pathology cross-sectionally ( Watermeyer et al, 2020 ). A unique aspect of the current study is the integration of longitudinal data, CSF AD biomarkers, and CBF.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies linking IIV to brain changes have shown that greater IIV relates to faster rates of cerebral atrophy in entorhinal cortex and hippocampus at follow-up ( Bangen et al, 2019 ) and more severe neurofibrillary tangle pathology and neuritic plaques ( Malek-Ahmadi et al, 2017 ). In contrast, another recent study found that IIV was not associated with cerebrospinal fluid (CSF) based markers of amyloid ( Watermeyer et al, 2020 ). There have been no studies published to date examining baseline IIV associations with early cerebrovascular damage such as reduced cerebral blood flow (CBF) using arterial spin labeling (ASL) magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This article is intended solely for the personal use of the individual user and is not to be disseminated broadly. Holland, 2018;Watermeyer et al, 2020Watermeyer et al, , 2021. We encourage researchers to extend our investigation to examine age-related compensatory strategies that may occur in response to cognitive senescence.…”
Section: Tablementioning
confidence: 99%
“…Importantly, estimation of within-person cognitive dispersion based on neuropsychological procedures is simple and cost-effective for clinicians (Holtzer et al, 2008). In particular, the adoption of these indices would repurpose familiar and currently available neuropsychological tools to potentially optimize their sensitivity and specificity for dementia detection (Gleason et al, 2018; Holtzer et al, 2008; Watermeyer et al, 2020), thereby relieving clinical and research groups from the pressures surrounding the implementation of novel assessment protocols, such as expertise acquisition through staff training. This may be particularly pertinent to areas of the country or world where resources for such activities are limited (e.g., developing nations).…”
mentioning
confidence: 99%